A Study on Clique Invariants of Jaco-Type Graphs - Seles, M. Jerlin; Mary, U.; Kok, Johan (Communications in Mathematics and Applications, 2016)
The first study related to this concept was that on primitive holes [2]. A primitive hole is indeed the study of the existence of 3-cliques. In this paper we report on research in respect of clique parameters and related properties thereof forcertain Jaco-type graphs.